Stefan Zweig A Bibliography - Klawiter, Randolph J. (UNC Studies in the Germanic Languages and Literatures, 1965)
Originally published in 1965, this volume presented the only comprehensive bibliography of the writings of the Austrian novelist, journalist, and playwright Stefan Zweig and of the books and articles about his work.